10.2: A Novel GOA Providing Both Emission‐controlled PWM Signal and Switch‐controlled Scan Signal for AMOLED Displays. (26th August 2021) - Wang, Zhichong; Feng, Jing; Liu, Peng; Luan, Xinglong; Chang, Chuanchuan; Yuan, Guangcai
Abstract : For the purpose of simplifying the gate driver on array for AMOLED panels using p‐LTPS or LTPO TFTs, a novel shift register module circuit was developed. Integrating the module with the common‐used EM GOA, a simplified GOA integrated both functions for generating emission‐controlled n‐type EM signal and switch‐controlled scan signal was developed. The feasibility of the proposed circuit was demonstrated through simulations results.